Peran Komunikasi Keluarga dalam Mengantisipasi Kenakalan Remaja - Dyen Novita Ilmy; Dr. Anang Anas Azhar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this research is to understand the role of family communication in anticipating juvenile delinquency. This study uses a qualitative descriptive research method. The research data was taken from interviews with 3 informants. The results of this study are that according to all informants, family communication is the most important thing, and the closeness between parents and children is the key to everything. The conclusion of this study is that in anticipating juvenile delinquency parents/families always prioritize communication between parents and their children. With in-depth heart-to-heart communication, as a parent, you will be able to understand what your child wants and vice versa, your child will understand what your parents want. Keywords: Adolescents, Communication, Family